A Quantitative Procedure for Multi-Object Investigation of Short and Simple Signatures - A. A. Smirnov (Теория и практика судебной экспертизы, 2018)
Multiple short and simple signatures have not previously been the subject of a separate study. Traditional approaches are usually insufficient for the analysis of such signatures. The author presents a methodology that will improve the effectiveness of handwriting examination of short and simple signatures, and help the court and the investigation to obtain convincing evidence to establish the material circumstances of the case. The premises and rationale, experimental data, and mathematical apparatus are described, along with the range and mode of application of the automated quantitative methodology for multi-object examination of short and simple signatures.